PSYCHOSOCIAL REPERCUSSIONS OF THE COVID-19 PANDEMIC FOR MOTHERS OF CHILDREN WITH AUTISM SPECTRUM DISORDER - Teixeira, Olga Feitosa Braga; Rocha, Fabiana Lucena; Silva, José Wagner Martins da; Pessoa, Vera Lúcia Mendes de Paula; Miranda, Karla Corrêa Lima (Cogitare Enfermagem, 2023)
Objective: to understand the psychosocial repercussions of the COVID-19 pandemic for mothers of children with Autism Spectrum Disorder. Method: a qualitative study, with participation of 22 mothers. The data were collected from May to July 2022 in the inland of Paraíba, Brazil, through the Dynamics of Creativity and Sensitivity. The analysis took place through the theoretical-analytical framework of French discourse analysis. Results: fear, anxiety, anguish and concerns assumed a central place in the mothers' dialogical movement. Faced with the demands and reconfigurations in the routine, there was physical, emotional and psychological overload, with repercussions on maternal life. Loneliness can be seen in the weak or non-existent support network during the pandemic. Conclusion: the study can support reflection on the repercussions of the pandemic on the lives of mothers of children with autism and enable the development of actions that prioritize mental health, helping them to overcome moments of adversity.